2022
DOI: 10.1186/s13075-022-02920-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiovascular risk on the diagnostic accuracy of the ultrasound Halo Score for giant cell arteritis

Abstract: Objective To evaluate the impact of cardiovascular risk (CVR) on the diagnostic accuracy of the ultrasonographic (US) Halo Score in patients with suspected giant cell arteritis (GCA). Methods Retrospective observational study of patients referred to our US fast track clinic with suspected GCA for a 2-year period. The intima-media thickness (IMT) of cranial and extra-cranial arteries and the Halo Score was determined to assess the extent of vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Cut-off values for the thickness of the intima-media complex have been proposed for follow-up studies (common superficial temporal artery 0.42–0.44 mm, parietal branch 0.29–0.36 mm, frontal branch 0.34 mm, axillary artery 1.0 mm (0.9 mm for chronic vasculitis)) 55–58. They may also aid in distinguishing normal from acute or chronic vasculitis; however, further studies are required to validate these values, particularly in people with advanced age or with severe arteriosclerosis 59–61…”
Section: Resultsmentioning
confidence: 99%
“…Cut-off values for the thickness of the intima-media complex have been proposed for follow-up studies (common superficial temporal artery 0.42–0.44 mm, parietal branch 0.29–0.36 mm, frontal branch 0.34 mm, axillary artery 1.0 mm (0.9 mm for chronic vasculitis)) 55–58. They may also aid in distinguishing normal from acute or chronic vasculitis; however, further studies are required to validate these values, particularly in people with advanced age or with severe arteriosclerosis 59–61…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have shown higher IMT levels in patients with atherosclerosis, with at least one TA segment above published cut-off values in approximately 10–20% of patients at high to very-high cardiovascular risk (CVR) (according to the European Society of Cardiology (ESC) 2021 classification) ( 25–28 ). Higher halo scores have also been described in non-GCA patients with high to very-high CVR ( 28 , 29 ). CVR is therefore expected to influence the diagnostic performance of IMT cut-off values, which is particularly relevant because high CVR is very prevalent in the age group of patients with GCA ( 28 , 30 ).…”
Section: Introductionmentioning
confidence: 85%
“…Higher halo scores have also been described in non-GCA patients with high to very-high CVR ( 28 , 29 ). CVR is therefore expected to influence the diagnostic performance of IMT cut-off values, which is particularly relevant because high CVR is very prevalent in the age group of patients with GCA ( 28 , 30 ).…”
Section: Introductionmentioning
confidence: 85%
“…IMT may be slightly greater in patients with arteriosclerosis even when outside arteriosclerotic plaques. 98 , 104 …”
Section: Ultrasound For Disease Monitoringmentioning
confidence: 99%